Constructing Br-Doped Li10SnP2S12-Based All-Solid-State Batteries with Superior Performances - Qiyue Luo; Liang Ming; Dong Zhang; Chaochao Wei; Zhongkai Wu; Ziling Jiang; Chen Liu; Shiyu Liu; Kecheng Cao; Long Zhang; Chuang Yu; Shijie Cheng (Energy Material Advances, 2023)
Ionic conductivity and electro/chemical compatibility of Li10SnP2S12 electrolytes play crucial roles in achieving superior electrochemical performances of the corresponding solid-state batteries. However, the relatively low Li-ion conductivity and poor stability of Li10SnP2S12 toward high-voltage layered oxide cathodes limit its applications. Here, a Br-substituted strategy has been applied to promote Li-ion conductivity. The optimal composition of Li9.9SnP2S11.9Br0.1 delivers high conductivity up to 6.0 mS cm−1. 7Li static spin-lattice relaxation (T1) nuclear magnetic resonance (NMR) and density functional theory simulation are combined to unravel the improvement of Li-ion diffusion mechanism for the modified electrolytes. To mitigate the interfacial stability between the Li9.9SnP2S11.9Br0.1 electrolyte and the bare LiNi0.7Co0.1Mn0.2O2 cathode, introducing Li2ZrO3 coating layer and Li3InCl6 isolating layer strategies has been employed to fabricate all-solid-state lithium batteries with excellent electrochemical performances. The Li3InCl6-LiNi0.7Co0.1Mn0.2O2/Li3InCl6/Li9.9SnP2S11.9Br0.1/Li-In battery delivers much higher discharge capacities and fast capacity degradations at different charge/discharge C rates, while the Li2ZrO3@LiNi0.7Co0.1Mn0.2O2/Li9.9SnP2S11.9Br0.1/Li-In battery shows slightly lower discharge capacities at the same C rates and superior cycling performances. Multiple characterization methods are conducted to reveal the differences of battery performance. The poor electrochemical performance of the latter battery configuration is associated with the interfacial instability between the Li3InCl6 electrolyte and the Li9.9SnP2S11.9Br0.1 electrolyte. This work offers an effective strategy to constructing Li10SnP2S12-based all-solid-state lithium batteries with high capacities and superior cyclabilities.